Predatory thrips species composition, their prey and host plant association in Northern Thailand - Saengyot, Samaporn (Agriculture and Natural Resources, 2016)
A survey of predatory thrips, their prey and associated host plants was carried out from February 2013 to February 2014 in Chiang Rai, Phayao, Chiang Mai, Lamphun and Lampang provinces in Northern Thailand. The survey revealed 10 species of predatory thrips in 5 genera in the Family Phlaeothripidae. They were: Aleurodothrips fasciapennis (Franklin), Androthrips flavipes Schmutz, Androthrips ramachandrai Karny, Karnyothrips flavipes (Jones), two indeterminate Karnyothrips sp.1 and sp.2, Leptothrips sp., Podothrips lucasseni (Krüger), and two indeterminate Podothrips sp. 1, and sp. 2. Eleven species of insect and mite pests serving as prey were found associated with 16 species of host plants in 13 families. They were: scale insects, Coccus viridis (Green) and two Coccus spp.; spiraling whitefly, Aleurodicus dispersus Russell; unidentified gall-making Hemiptera; coffee berry borer, Hypothenemus hampei (Ferrari); unidentified crambid lepidopterous larvae; Kanzawa spider mite, Tetranychus kanzawai Kishida; santol gall mite, Eriophyes sandorici Nelepa; litchi rust mite, Aceria litchii (Keifer); and bamboo green mite, Aponychus corpuzae Rimando. The findings from this investigation could provide basic information necessary for further investigation in the use of some of these predatory thrips as biological control agents of insect and mite pests of economic importance in Thailand.